SPEECH ACTS IN INDONESIAN AUTOMOTIVE ADVERTISEMENTS AND ITS FUNCTIONS IN PERSUADING THE CONSUMERS - Gracia Cyntia Febe Yolanda; Yuli Widiana (Universitas Katolik Widya Mandala Surabaya, 2023)
This qualitative descriptive research analyzes the speech acts in automotive advertisements aired on Indonesian television from 2021 to 2022 and explores their functions. The study focuses on the types of speech acts prevalent in automotive advertisements and their roles in persuading consumers and achieving sales goals. Data were collected from automotive advertisements on television programs in Indonesia and classified into assertive, directive, expressive, and commissive speech acts. The functions of these speech act in Indonesian automotive advertisements were identified as demonstrating products with a positive image, persuading consumers to make purchases, developing emotional and entertaining appeals, and building trust among potential consumers. By employing appropriate speech acts, advertisers can effectively convey the benefits and attractiveness of their products to consumers, potentially increasing sales and achieving marketing success. The research findings reveal that commissive speech acts were the most frequently used in motorcycle advertisements, aiming to motivate immediate purchases by promising benefits or additional advantages. On the contrary,assertive speech acts were the least utilized in automotive advertisements on television because this type of speech acts focuses more on conveying information or facts so it is less on persuading or influencing the behavior of the audience.This study sheds light on the dominance of commissive speech acts in Indonesian automotive advertisements and their significant role in influencing consumers by emphasizing the advantages and benefits of the promoted automotive products. Understanding and employing appropriate speech acts can greatly enhance marketing efforts in the automotive industry.